Perceptions of organizational communication processes in quality management - Arnold, Esther (2011)
Language is a natural psychological phenomenon, indispensable to all humans in society. This article presents the theoretical foundations on communication in process quality management, bringing studies dealing with communication and ISO 9001:2000 management, aiming at investigating how these variables have been perceived in organizations. The importance of the steps that should permeate the communication process is highlighted through published research, concluding on the need for studies that demonstrate the importance of subjectivity in the communication process, a present phenomenon in any interpersonal relationship.